0001 The Innervation Of Hypoglossal Motoneurons That Originates From A7 And/or Subcoeruleus Noradrenergic Neurons Is Impaired In Mice Treated With Chronic Intermittent Hypoxia. (12th April 2019) - Rukhadze, Irma; Gvritishvili, Anzor; Kvizhinadze, Maya; Fenik, Victor B
Abstract: Introduction: Noradrenergic (NA) neurons of A7 and SubCoeruleus (SubC) pontine nuclei project to the hypoglossal (XII) nucleus and provide excitatory input to XII motoneurons that play a role in the pathology of obstructive sleep apnea (OSA). We sought to investigate whether chronic intermittent hypoxia (CIH), one of the major morbid factors of OSA, affects the NA innervation of XII motoneurons that originates from A7 and SubC neurons. Methods: We used five DBH-cre mice that received unilateral injections (100 nl) of an adeno-associated viral (AAV) vector (AAV8-EF1a-DIOhChR2(H134R)-mCherry) aiming at A7 region and were exposed to CIH (O2: 10% 4 min/21% 3 min, 10 hours daily for 35 days; 3 mice) and sham control (2 mice). After the exposure, animals were perfused and brainstem sections processed for tyrosine-hydroxylase and DsRed immunohistochemistry. We calculated the number of DsRed-positive neurons in A7/SubC regions and the number of DsRed-positive axonal projections within the dorsal and ventral compartments of XII nucleus at rostral, central and caudal antero-posterior levels, ipsi- and contra-laterally to the injected side. The DsRed-positive fibers that visually appeared as thick and thin were counted separately. Results: The average proportion of AAV-transfected NA neurons found in SubC and A7 nuclei was similar in CIH- (SubC/A7=1.4) and sham-treated mice (SubC/A7=1.3). In all mice, the mean ratio of "thin"/"th ick" fibers was higher in ventral compartments ("thin"/"thick"=2.7) as compared to dorsal compartments ("thin"/"thick"=1.0, p<0.05) calculated at all three levels of XII nucleus. In CIH-treated mice, numbers of the "thin" fibers within the ventral compartments on ipsilateral side at the rostral and caudal levels, and on contralateral side at the central level, were 50-60% of that calculated in sham-treated mice. The "thick" fibers did not show a consistent trend between CIH- and sham-treated mice. Conclusion: These data suggest that CIH may have detrimental effects on the NA innervation of the ventral compartment of the XII nucleus by A7/SubC nuclei, which would further impair the patency of upper airway muscles in OSA patients. Support (If Any): R01HL133847